Implikasi Perjanjian Perkawinan Sebagai Perlindungan Harta Bersama Dan Hak Pada Suami Istri Sebagai Pelaku Usaha Persekutuan Komanditer (Cv) - Yosephine Adinda Dwika Sandra; Anjar Sri Ciptorukmi Nugraheni (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2024)
This research aims to analyze the form of protection for joint assets and the rights of each party in the marriage agreement as well as the implications of the marriage agreement for husband and wife in limited partnership (CV) businesses. The research method used by the researcher is normative research with prescriptive research characteristics whose research approach is a statutory approach and a case approach. The data collection technique used is literature study, with the syllogism method and deductive thinking as an analysis technique. The results of the research highlight the role of marriage agreements as a form of protection not only for joint assets but also the rights of husband and wife business actors, especially CVs. Apart from that, it was also found that the marriage agreement was a form of protection from the risks associated with the CV business.